NEW VARIETY OF ONGONITE - Dergachev V.B. (My University, 1988)
Dikes of ultrarare-metal microgranophyre similar to ongonite were recently detected in western Siberia. They are confined to a northeast-striking belt that cuts a hypabyssal granite pluton and is concordant with the dominant strike of associated quartz-wolframite veins and greisen bodies. In this belt, besides post-granite dikes of geochemically diverse microgranite porphyry and granite porphyry and isolated bodies of aplite, pegmatite and microgranite, there are pre-granite dikes of albitite, quartz albitite and albite-granite porphyry, which indicate its prolonged development. Of 131 dikes studied, the pre-granite account for 13.7 percent of them, the granite porphyry for 10 percent and the microgranite porphyry for 76.3 percent. The latter dikes, except for the ongonite, form a complementary series and can be subdivided into ultrarare-metal (ongonite-type) 7 percent, elvan (quartz porphyry) 28, rare-metal 39, subrare-metal 11, and standard 15.